DEEP STRUCTURE OF THE CRUST ALONG THE FENNOSCANDIA-SARMATIA JUNCTION ZONE (CENTRAL BELARUS): RESULTS OF A GEOPHYSICAL-GEOLOGICAL INTEGRATION - Kozlovskaya E.; Taran L.N.; Karatayev G.I.; Yliniemi J.; Giese R. (My University, 2002)
The EUROBRIDGE'96 seismic refraction and wide-angle reflection profile in Belarus crosses the 2.0–1.9 Ga Palaeoproterozoic Central Belarus belt (CB) subdivided by NE-trending Minsk Fault into the northwestern (NWCB) and southeastern (SECB) sub-terranes differing in their styles of tectonothermal evolution. The first interpretation of the EUROBRIDGE'96 profile, however, did not indicate any difference between the NWCB and SECB and revealed a high-velocity zone beneath the SECB, with a P-wave velocity of 6.6 km/s at a depth of 6 km, which does not correlate with any pronounced positive Bouguer anomaly. We present a detailed analysis of the seismic and gravity data obtained along the EUROBRIDGE'96 profile, complemented with petrological and petrophysical observations on the main rock types of the CB. Our integrated interpretation shows that the dip orientation of the main reflectors and the P-wave velocity and density are different in the NWCB and SECB. The Minsk Fault zone is distinguished as an area of relatively high velocities (>6.2 km/s) in the upper crust. Increased reflectivity in the middle crust SE of the Minsk Fault may be explained by a laminated structure composed of alternating tectonically deformed amphibolite-facies and granulite-facies rocks that produce a certain seismic anisotropy. This seismic anisotropy is proposed as an alternative explanation for the high P-wave velocity in the middle crust beneath the SECB that does not result in any corresponding positive gravity anomaly. The laminated structure beneath the SECB might be formed during the uplift of the NWCB and juxtaposition of the NWCB and SECB.